The relationship between corporate entrepreneurship and strategic management - Barringer, Bruce R.; Bluedorn, Allen C. (Strategic Management Journal, 1999)
This study examines the relationship between corporate entrepreneurship intensity and five specific strategic management practices in a sample of 169 U.S. manufacturing firms. The five strategic management practices include: scanning intensity, planning flexibility, planning horizon, locus of planning, and control attributes. The results of the study indicated a positive relationship between corporate entrepreneurship intensity and scanning intensity, planning flexibility, locus of planning, and strategic controls. The fine-grained nature of these results may be of practical use to firms that are trying to become more entrepreneurial and may help researchers better understand the subtleties of the interface between strategic management and corporate entrepreneurship. Copyright © 1999 John Wiley & Sons, Ltd.